Corrosion Behavior of Mg-Al/TiC Composites in NaCl Solution. (10th February 2011) - Falcon, L. A.; Bedolla B., E.; Lemus, J.; Leon, C.; Rosales, I.; Gonzalez-Rodriguez, J. G.
Abstract : The corrosion behavior of TiC particles reinforced Mg-Al alloy in 3.5% NaCl solution has been evaluated using electrochemical techniques. Tested alloys included an Mg-9Al (Mg AZ91E) alloy with and without 56 wt. % TiC particles. Electrochemical techniques included potentiodynamic polarization curves, linear polarization resistance, electrochemical noise, and electrochemical impedance spectroscopy measurements. All techniques showed that the composite exhibited a lower corrosion rate than the base alloy. Evidence of galvanic effects that increased the composite corrosion rate was found between the matrix and the TiC particles. Additionally, the tendency to suffer from pitting corrosion was higher for the base alloy than that for the composite. Electrochemical impedance results showed the importance of adsorption/diffusion phenomena in both materials.